2015
DOI: 10.1155/2015/139451
|View full text |Cite
|
Sign up to set email alerts
|

Magnolia officinalisExtract Contains Potent Inhibitors against PTP1B and Attenuates Hyperglycemia in db/db Mice

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is an established therapeutic target for type 2 diabetes mellitus (T2DM) and obesity. The aim of this study was to investigate the inhibitory activity of Magnolia officinalis extract (ME) on PTP1B and its anti-T2DM effects. Inhibition assays and inhibition kinetics of ME were performed in vitro. 3T3-L1 adipocytes and C2C12 myotubes were stimulated with ME to explore its bioavailability in cell level. The in vivo studies were performed on db/db mice to probe its anti-T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…C2C12 myoblasts culture and differentiation were performed as our previously published. 13 In brief, C2C12 myoblasts were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM), supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin (PS) at 37°C in humidified atmosphere with 5% CO 2 . For differentiation, C2C12 myoblasts were cultured to 75% confluence in DMEM with 10% FBS, 1% PS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C2C12 myoblasts culture and differentiation were performed as our previously published. 13 In brief, C2C12 myoblasts were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM), supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin (PS) at 37°C in humidified atmosphere with 5% CO 2 . For differentiation, C2C12 myoblasts were cultured to 75% confluence in DMEM with 10% FBS, 1% PS.…”
Section: Methodsmentioning
confidence: 99%
“…12 In our previous study, we validated the antidiabetic activity of Magnolia bark. 13 Honokiol is proved to be the pharmacologically effective component 12 with the potent activity of antioxidant, anti-inflammatory, antibacterial, antitumor, and antianxiety antithrombotic. 14 17 Recently, Atanasov et al 18 demonstrated that honokiol functions as a novel nonadipogenic partial PPAR-γ activator in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Using a type 2 diabetes (T2DM) mouse model established by high-fat diet (HFD) combining with streptozotocin (STZ) injection, Sun et al [17] demonstrated that oral gavage of honokiol at dose of 200 mg/kg once per day for 8 weeks significantly decreased the blood glucose levels. Sun et al [5] also investigated the effect of Magnolia officinalis extract on blood glucose level of db/db mice which have been recognized as a model of T2DM. The authors found that Magnolia extracts (ME) treatment once a day at dose of 0.5 g/kg for 4 weeks attenuates hyperglycemia in db/db mice.…”
Section: The Effect Of Magnolia Genus On Blood Glucosementioning
confidence: 99%
“…Sun et al [5] demonstrated that in vitro treatment with Magnolia officinalis extracts enhanced the phosphorylation of insulin receptor β-subunit (IRβ) in response to insulin stimulation in 3T3-L1 adipocytes and C2C12 myotubes by suppressing the activity of protein tyrosine phosphatases 1B, which finally resulted in enhanced insulin-stimulated glucose transporter 4 (GLUT4) translocation and extracellular signal-regulated kinases phosphorylation. Furthermore, it has been reported that honokiol can act as an agonist of peroxisome proliferator-activated receptor gamma, which plays an important role in regulation of glucose homeostasis [14].…”
Section: The Effect Of Magnolia Genus On Blood Glucosementioning
confidence: 99%
See 1 more Smart Citation